Self-Build Homes - Benson, Michaela; Hamiduddin, Iqbal (UCL Press, 2017)
Self-Build Homes connects the burgeoning interdisciplinary research on self-build with commentary from leading international figures in the self-build and wider housing sector. Through their focus on community, dwelling, home and identity, the chapters explore the various meanings of self-build housing, encouraging new directions for discussions about self-building and calling for the recognition of the social dimensions of this process, from consideration of the structures, policies and practices that shape it, through to the lived experience of individuals and households. Divided into four parts - Discourse, Rationale, Meaning; Values, Lifestyles, Imaginaries; Community and Identity; and Perspectives from Practice - the volume comes at a time of renewed focus from policy managers and practitioners, as well as prospective builders themselves, on self-build as a means for producing homes that are more stylised, affordable and appropriate for the specific needs of households. It responds to recent advances in housing and planning policy, while also bringing this into conversation with interdisciplinary perspectives from across the social sciences on housing, home and homemaking. In this way, the book seeks to update understandings of self-build and to account for housing as a distinctly social process.